Wide‐Range and High‐Stability Flexible Conductive Graphene/Thermoplastic Polyurethane Foam for Piezoresistive Sensor Applications. Issue 10 (29th June 2021) - Lü, Xiaozhou; Yu, Tingting; Meng, Fancheng; Bao, Weimin
Abstract: Flexible pressure sensors based on thermoplastic polyurethane (TPU) conductive polymer foam can be applied to health monitoring, motion detection, and electronic skin. For satisfying the demand of long‐term use in high‐pressure range, the TPU conductive polymer foam requires improvements in detection range, stability, and repeatability. In this paper, a flexible conductive reduced graphene oxide (rGO)/thermoplastic polyurethane (TPU) porous foam with ultra‐wide pressure detection range and high‐stability is proposed. First, an elastic and flexible TPU polymer foam matrix is fabricated via freeze‐drying. Then, the rGO/TPU foam is prepared by dip‐coating it into graphene oxide (GO) solution followed by chemical reduction. The electromechanical properties of the foam are studied by gradual and cyclic compression tests, thereby investigating the influence of different rGO loadings on the properties of the foam. Experimental results suggest that the prepared foam possesses outstanding performance in pressure detection range (20 kPa to 1.94 MPa), sensitivity (0.0152 kPa −1 ), response (166 ms), and stability (>10 000 cycles, at 0–35 kPa), satisfying the demand of long‐term use in high‐pressure range. The foam being assembled as a wearable pressure sensor to monitor human motions exhibits satisfactory performance, offering potential for high‐pressure detection and high‐stability electronic sensing devices. Abstract : A flexible conductive reduced graphene oxide (rGO)/thermoplastic polyurethane (TPU) porous foam with ultra‐wide pressure detection range and high‐stability is proposed. The rGO/TPU foam possesses outstanding performance in pressure detection range (20 kPa to 1.94 MPa), sensitivity (0.0152 kPa −1 ), and stability (>10 000 cycles), satisfying the demand of long‐term use in high‐pressure range.